Scar endometriosis presenting as a painful abdominal mass - Li- Yung Chen; Sheng- Der Hsu (Wolters Kluwer Medknow Publications, 2020)
Abdominal wall scar endometriosis occurs in 1%-2% of women following a cesarean section delivery. We report a case of a 36-year-old woman with scar endometriosis, presenting with an acute, painful abdominal wall mass. She underwent a cesarean section 8 years before presentation. She was admitted to the emergency room for physical examination of the abdomen, which revealed a palpable mass. Abdominal computed tomography (CT) revealed an ill-defined soft-tissue lesion over the left rectus abdominis muscle (abdominal scar). Surgical removal of the abdominal wall mass was performed with adequate clearance margins with a preoperative diagnosis of postcesarean scar endometriosis. Postcesarean scar endometriosis is a rare cause of an abdominal mass; however, when this condition presents acutely, it can be difficult to diagnose. In this case, careful analysis of the patient's history, CT images, and histopathological results together confirmed the diagnosis. Surgical excision was performed under general anesthesia while maintaining adequate clearance margins.